OPTIMALISASI UMKM RAJA BOLU - Irwandi, Irwandi; Samsir, Andi; Syachbrani, Warka; Ryketeng, Masdar; Oktaviyah, Nurafni (LPPM Universitas Flores, 2024)
MSMEs play an important role in creating jobs and contributing to the economy. Small and medium enterprises are used as a valuable opportunity to make money more profitably. Bolu is a very popular food in Indonesia. Steamed sponge cake has different variations, such as coconut milk, sugar, pandan leaves, and bananas.